Pemikiran Fatchur Rahman Mengenai Skema Sanad Hadis Dalam Buku Ikhtisar Mushthalahul Hadits - Faisal, Ahmad; Hazaa, Zuhair Mubarrak (Institut Agama Islam Sumatera Barat Pariaman, 2024)
This research aims to explore more deeply the thought of Fatchur Rahman's hadith. This research is qualitative research, library research in nature, so the primary source is Fatchur Rahman's written work entitled Ikhtishar Mushthalahul Hadith. Fatchur Rahman explains the limited definition of Hadith and the definition of Hadith from a more general perspective. Fatchur Rahman doesn't seem interested in discussing more broadly the differences between Hadith and Sunna, but Fatchur Rahman is more inclined to equate Sunna and Hadith. The definition of Hadith with a limited meaning according to Fatchur Rahman is: